DETERMINAN NILAI PERUSAHAAN SEKTOR BAHAN BAKU SEBELUM DAN DI MASA PANDEMI COVID-19 - Edmanata, Patricia Vida; Yanti, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research was conducted to see how the influence of capital structure, profitability, firm size, and liquidity on company value in raw material sector companies listed on the Indonesia Stock Exchange during 2018-2021 before and during the Covid-19 pandemic. Samples were taken by purposive sampling method and obtained a total of 25 companies as samples. All data is processed using Microsoft Excel 2019 and SPSS (Statistical Product and Service Solution). The results for the period before the Covid-19 pandemic showed that capital structure, profitability, liquidity did not affect company value, while firm size did affect company value. The results for the period during the Covid-19 pandemic showed that capital structure, profitability, and firm size had an effect on company value, while liquidity had no effect on company value. In a different test, the results showed there was no difference in company value before and during the Covid-19 pandemic. The implication of this research is that it is important for companies to pay attention to factors such as firm size which can increase company value and have a good impact on investor valuation.